ANALISA PROSES PRODUKSI PERSENJATAAN PADA INDUSTRI SELONGSONG PELURU GUNA MEMPERKUAT PERTAHANAN NASIONAL - Hanjayani, Maladi; Judijanto, Judijanto; Sarkolim, Sarkolim (Journal of Industrial Engineering & Management Research, 2022)
Large countries generally have large defenses and militaries as well. In a study, it was shown that one of the indicators of the assessment that the country was considered great was its military strength and completeness. The average time it takes to make 1 sleeve is 10 seconds. However, in data collection, the lathe process takes a longer time than other processes, which is 19-20 seconds. With this condition, the production results from the previous station will accumulate and the next station will have a waiting time. This is called an unbalanced production line. With this condition, line balancing must be carried out so that production results are maximized. The improvements planned by the researchers to make the production line more balanced are by adding a lathe line. By adding a line lathe, the cycle time is balanced. Thus the production process can run well and smoothly.